A network-based analysis to identify a piRNA-target signature related to colorectal cancer prognosis: in silico and in vitro study - Fatemeh Khavari; Rezvan Najafi; Saeed Afshar; Akram Jalali; Mehrdad Hashemi; Alireza Soltanian; Fatemeh Nouri (Discover Oncology)
Abstract Purpose Patients with colorectal cancer (CRC) are diagnosed in advanced stages and have worse overall survival. Also, this cancer incidence is rising in many countries. The aim of this study is to find piwi-interacting RNAs (piRNA) predicting the prognosis of patients with colorectal cancer, using bioinformatics and evaluating these results through RT-qPCR method. Methods The target genes of piRNAs were predicted using miRDB and TargetRank databases. Protein–protein interaction (PPI) networks were constructed by STRING and were analyzed with Cytoscape software and the MCODE tool used for module construction. Expression levels of final selected piRNAs in 18 pairs of CRC tissue and adjacent normal tissue were measured by quantitative real-time reverse-transcription polymerase chain reaction (qRT-PCR). Results Twenty CRC-related piRNAs and 980 target genes were included in this study. After PPI analysis 19 hub genes were identified. Then, the prognostic value of these hub genes was assessed via Kaplan–Meier survival analyses. This survival analysis indicated that the expression of six genes was significantly associated with overall survival of patients with CRC. These genes are targets of hsa-piR-487, hsa-piR-28944 and piR-hsa-8401. Also, the pathway analysis revealed the potential signal pathways of these piRNAs targets involved in CRC. RT-qPCR showed that hsa-piR-487 and hsa-piR-28944 expression significantly were down-regulated in CRC tumor tissues compared with the adjacent normal tissues (P < 0.05, P < 0.01). Conclusion It seems that hsa-piR-487 and hsa-piR-28944 can be considered as a potential biomarker for the diagnosis of CRC. However, it is still necessary to conduct studies with a higher statistical population and measure them in the serum of patients to confirm these results.